Quadratic estimating functions for Nbingarch model - Mohamed, Ibrahim; Mohamad, Nurul Najihah; Thavaneswaran, A.; Ng, Kok Hau (2019)
Time series of counts has been widely used in many real-world applications. In this paper, we derive the quadratic estimating functions for negative binomial GARCH, known as NBINGARCH (p,q) model. Specifically, we derive the optimal function of NBINGARCH(1,1) and obtain the estimated parameters of interest via simulation. We show that the performance of the quadratic estimating functions method is superior compared to estimating functions and maximum likelihood methods. For illustration, we fit the NBINGARCH(1,1) on the poliomyelitis cases in the United State from 1970 to 1983.